Estrategia educativa para mejorar la convivencia escolar en relación con la práctica de valores en los estudiantes del nivel de educación básica superior de la sección vespertina de la unidad educativa experimental Bernardo Valdivieso. Período 2012-2013 - Belizaca Cabrera, José Antonio (2015)
This research entitled: Educational Strategy for Improving School Coexistence in relation to the Securities Practice level students of Basic Education Superior, afternoon section of the Experimental Education Unit Bernardo Valdivieso, period 2012-2013, has the general objective: to design an educational strategy to improve school coexistence and harmonious relationship with Securities Practice students of Basic Education Level Superior, afternoon section of the Experimental Education Unit Bernardo Valdivieso. 2012-2013. The methods used were: inductive, deductive, analytic, synthetic, triangulation and statistical; to collect field data, technical survey it was applied the month of March 2014-5 authorities, 28 teachers, 19 parents and 107 students was used; the instrument constituted a pre-questionnaire designed for this purpose. The analysis of the results regarding the existence of the Code of Coexistence of the institution identified that teachers who are fitter know him; well, the same teachers were those who made a major contribution to the process of socialization; and are the students who have less information about it. The values of the Code of Coexistence that reconcile the requirements of society, the authorities represents the highest percentage with the value of the health of society; whereas, for parents is the value of education for the exercise of citizenship; not, for the majority opinion of the educational actors, the values of education for democracy and culture of peace is true to a lesser extent. The value of the interaction of educational actors for a positive school coexistence; are the authorities who claim that they favor; however, for a certain group of teachers and students is met in part. On the list of values promoted by the Code of Coexistence and what is practiced in the institution, for most educational stakeholders agree that the value of gender equality is the more he lives at school; however critical values that show less habit in practice, correspond to the values of punctuality, respect, responsibility, solidarity, honesty, justice and peace culture. To find out about the practice of the values instilled teachers in the classroom, to project the family and society, parents in a representative percentage say yes it is true. On the main suggestions of educational actors for better participation to strengthen the practice of values, most suggest workshops, also contribute to a better educational interaction in the school community, updating the Code of Coexistence, the psychological support of the Department of Student Counseling and guide the best pedagogical treatment of the values in the classroom lectures. Finally, after running the alternative proposal, through a seminar-workshop critical values, systemic analysis of research, we proceeded to test the hypothesis, concluding that yes, an educational strategy based on the practice of values applies students in Basic Education Level Superior, afternoon section of the Experimental Education Unit Bernardo Valdivieso. Period 2012-2013, due to improvements in the School Coexistence evidence, proving the hypothesis.